Sediment Particle Size Composition in the Riparian Zone of the Three Gorges Reservoir - Liu, Dan; Nie, Qingyu; Xiong, Chunmei; Yu, Zhuolin; Lv, Yunan; Zhang, Shuai; Cheng, Shuxun; Lan, Bo; Kumar, Amit; Yu, Zhiguo; Lin, Junjie (Frontiers in Environmental Science, 2022)
The riparian zone is a transitional zone of terrestrial ecosystems and aquatic ecosystems, which is one of the main sources of reservoir sediment and pollutants. The sediment loss has an increasing trend in the riparian zone of the Three Gorges Reservoir (TGR), which was closely related to sediment particle size composition change in the riparian zone, but its distribution and factors are still unclear. Hydrological conditions, sediment particle size composition and vegetation properties in the riparian zone were investigated in 3 mainstream and 8 tributary sections along the Yangtze River within the TGR across 450 km. On the one hand, both sediment sand content and median particle size (D50) showed a horizontal raising trend from the upstream to the dam region of the TGR at the mainstream and tributary sites. On the other hand, compared to the upper-middle mainstream and the tributaries of Longxi, Wu, Longxi, Pengxi, Daning, Tongzi rivers, the D50 was much higher in the lower altitudes of the riparian zone in the tributaries of Wubu, Ruxi, and Xiangxi and the mainstream in the lower reaches of the Yangtze River. With the raising of the riparian zone slope, D50 decreased in the mainstream riparian zone sites, while increased in the tributary riparian zone sites (p < 0.05). Besides, D50 was 2.3 times higher in the south aspect relative to the north aspect of the riparian zone in the TGR. No significant relationship was found between root biomass of a local dominate species-Cynodon Dactylon (Linn.) and D50. Hydrological and geographical variables could predict 64%–67% of the D50 variance, and thus could be regarded as the main predictor of D50 in the riparian zone of the TGR.